A interação de entidades e redes de cooperação nas etapas de sensibilização, estruturação e manutenção : um estudo de caso na serra gaúcha - Andreola, Joceli Antônio (My University, 2014)
The purpose of this study is to explore and report interactions that take place between Cooperation Networks and corporations, during the stages of sensitization, structuring, and maintenance, identifying those corporations who interact with the Networks; maintaining relationships with corporations who started training processes and others; as for the interactions, whether they are all positive and in which stage there are more actions. To do so, a qualitative research was carried out, with an interview script and followed by content analysis. The Networks surveyed were selected according to economical segments pointed out according to their area in the Cooperation Network Program of the University of Caxias do Sul (UCS), the Corporations surveyed were chosen according to their references in the documentation generated on the Networks that were selected. It was possible to observe that the interactions and relationships are maintained along the stages with the controlling corporations and the High-Ed Institution carrying out the program, with a few Networks withdrawing for logistic matters; the other corporations contribute emphatically on the sensitization stage, helping in the mobilization of entrepreneurs, and on the maintenance stage, with actions on projects required by the Networks, with a highlight on managerial and technical qualification, and marketing actions. The reports collected from both Networks and Corporations place all these interactions as positive, in different moments, demonstrating little proximity of the Corporations with the Cooperation Network Program and its methodology, a fact that might work as leverage for more effective results of interactions from the determination of the emphasis and preponderance of these corporations on Cooperation Networks.
Este estudo objetiva explorar e relatar as interações que ocorrem entre Redes de Cooperação e entidades, nas etapas de sensibilização, estruturação e manutenção, identificando as entidades que interagem com Redes; a manutenção dos relacionamentos com entidades iniciadoras do processo de formação e outras; quanto às interações, se todas são positivas e em que etapa há mais ações. Para tal, foi realizada uma pesquisa qualitativa, com um roteiro de entrevistas e posterior análise de conteúdo. As Redes pesquisadas foram selecionadas conforme os segmentos econômicos destacados na área de execução, do Programa Redes de Cooperação, da Universidade de Caxias do Sul (UCS), as Entidades pesquisadas foram selecionadas através de suas menções na documentação gerada sobre as Redes selecionadas. Observou-se que as interações e os relacionamentos se mantêm, ao longo das etapas com a entidade controladora e a IES executora do Programa, com afastamento de algumas Redes por questões logísticas; as demais entidades contribuem, com ênfase, na etapa de sensibilização, auxiliando a mobilização dos empresários, e na etapa de manutenção, com ações sobre projetos demandados pelas Redes, com maior destaque à qualificação técnica e gerencial e ações mercadológicas. Os relatos de Redes e Entidades posicionam essas interações, todas positivas, em momentos diferentes, demonstrando pouca proximidade das Entidades com o Programa Redes de Cooperação e sua metodologia, fato que pode ser um ponto de alavancagem para resultados mais efetivos das interações a partir da determinação da ênfase e preponderância dessas entidades sobre Redes de Cooperação.
Keywords: Administração; Redes de cooperação; Entidades; Etapas da metodologia; Interação; Alianças estratégicas (Negócios), Planejamento estratégico; Cooperation networks; Corporations; Stages of the methodology; Interaction; Strategic alliances (Business); Strategic planning